AKTIVITAS EKSTRAK ETANOL DAUN KELOR (Moringa oleifera L.) PADA SEDIAAN SALEP BASIS ABSORPSI TERHADAP BAKTERI Propionibacterium acne - Maulana, Restu; Prabandari, Rani; Nawangsari, Desy (Jurnal Farmasi & Sains Indonesia, 2024)
Moringa leaves contain flavonoids, alkaloids, saponins and tannins that can inhibit bacterial growth. In order to make the use of moringa leaves more practical, an absorption base ointment formulation was made. Ointment preparations were chosen because they are suitable for medicinal purposes on the skin because the drug contact with the skin is longer. This study aims to determine the physical properties, stability and antibacterial activity of absorption base ointment preparations of moringa leaf ethanol extract. The research method is experimental laboratory. The extract concentrations used were F0 (base), F1 (15%), F2 (20%) and F3 (25%). Physical quality testing is seen from organoleptic, homogeneity, pH, spreadability and stickiness. The pH test results were sequentially obtained as 6.33 ± 0.15, 5.9 ± 0.1, 5.6 ± 0.1 and 5.56 ± 0.15. The spreadability test sequentially obtained 2.87 ± 0.07, 2.9 ± 0.05, 3.05 ± 0.05 and 3.25 ± 0.1 cm. The stickiness test was 17.60 ± 0.60, 17.59 ± 0.46, 16.87 ± 0.47 and 16.18 ± 0.56 seconds. The results were analyzed using SPSS 26 with One Way ANOVA, there were significant differences in pH values, spreadability and adhesiveness with a significance value of <0.05. The results of the stability test with the Cycling test method analyzed by T-test there was no significant difference from each formula between day 0 and day 12 with a 2-tailed value >0.05 which means that the formulas made are all stable in the stability test. Formula 1, 2 and 3 can inhibit Propionibacterium acne bacteria with an average inhibition zone of F1 10.34 ± 1.86 mm, F2 13.77 ± 3.43 mm and F3 16.67 ± 0.97 mm. It can be concluded that the three formulas have strong inhibition.